Materialização da formação ideológica contratualista no funcionamento discursivo jurídico-penal acusatório - Pires, Guilherme Moreira (2021)
The theme of this dissertation is the materialization of the contractualist ideological formation in the criminal law discourse, from the (oral) speech in plenary, in the city of Cascavel-PR. About this theme, there is the problematization: How does the contractualist ideological formation materialize in the Accusation speech at the Jury? The research is guided by the general objective of identifying and analyzing the functioning of the contractualist ideology “in defense of society” in the legal discourse of the Accusation at the Cascavel-PR Jury. Regarding the theoretical basis, this dissertation is supported by the Discourse Analysis of Michel Pêcheux, a materialist theory of discourse, in dialogue with the tradition (macrosociological) called Critical Criminology. Thus, dialectical materialism is being used as a method. The results of the study discursively explain the existence of the designated as contractualist ideological formation (idealistic philosophy) materialized in the analyzed criminal discourse, pointing out the impacts of this ideology (in tension with contemporary criminologies of critical matrices) in the criminal justice system. The present study is important in understanding the relationship between the ideological and the criminal field.